Pengaruh Customer Relationship Management dan Kepuasan Pelanggan Terhadap Loyalitas di Cafe Pelangi - Salamena, Allgreat Meidelia Clarista; Emanuel, Andi Wahju Rahardjo (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
This study aims to analyze the influence of Customer Relationship Management (CRM) implementation and customer satisfaction on customer loyalty at Cafe Pelangi. From 50 questionnaire respondents, the results of statistical analysis indicate that the implementation of CRM and customer satisfaction have a positive and significant impact on customer loyalty. All indicators of the CRM, customer satisfaction, and customer loyalty variables are valid and exhibit a high level of reliability. The data also meets the normality assumptions, allowing for the use of a multiple linear regression model. The regression results reveal that customer satisfaction significantly affects customer loyalty, with a coefficient of determination of 20.7%. This underscores the importance of enhancing customer satisfaction through CRM implementation to achieve a higher level of loyalty at Cafe Pelangi. These findings can serve as a strategic foundation for cafe management and other stakeholders to develop effective strategies in maintaining and expanding their market share
Keywords: Customer Relationship Management; Customer Satisfaction; Customer Loyalty; Cafe Business